2012
DOI: 10.1097/jgp.0b013e318246b6cb
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Improvement Following Treatment in Late-Life Depression: Relationship to Vascular Risk and Age of Onset

Abstract: Objectives To test the hypothesis that the degree vascular burden and/or age of onset may influence the degree to which cognition can improve during the course of treatment in late life depression. Design Measurement of cognition both prior to and following 12-weeks of treatment with Sertraline. Setting University Medical Centers (Washington University and Duke University) Participants 166 individuals with late life depression. Intervention Sertraline treatment. Measurements The cognitive tasks were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 39 publications
2
59
0
Order By: Relevance
“…Clinical and research experience shows that the cerebrovascular group probably suffers from recurrent or chronic depression and is difficult to treat with limited therapeutic success (Barch et al, 2012;Ligthart et al, 2012;O'Brien, 2006;Sneed et al, 2007). Several research groups have, however, failed to identify vascular depressed persons in general or clinical populations (Naarding et al, 2007;Valkanova & Ebmeier, 2013).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Clinical and research experience shows that the cerebrovascular group probably suffers from recurrent or chronic depression and is difficult to treat with limited therapeutic success (Barch et al, 2012;Ligthart et al, 2012;O'Brien, 2006;Sneed et al, 2007). Several research groups have, however, failed to identify vascular depressed persons in general or clinical populations (Naarding et al, 2007;Valkanova & Ebmeier, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…Consequently, clinical management of vascular depression would be aimed not only at treating depressive symptoms, but also involve cardiovascular risk management. Indeed, recent research findings suggest that the outcome of current treatment protocols in 'vascular depressed' older people is insufficient and that vascular depression often shows a more chronic course (Barch et al, 2012;Hajjar et al, 2009;Paulson & Lichtenberg, 2012). Furthermore, it has been stated that vascular depression is prodromal to frailty and could eventually turn into vascular dementia (Brunnstr€ om, Passant, Englund, & Gustafson, L, 2013;Paulson & Lichtenberg, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…The authors concluded that cognitive deficits in late-life depression persist over months to years, affect multiple domains, and are a manifestation of trait rather than state effects of depression. Barch and colleagues [20], on the other hand, examined individuals with late life depression both prior to and following treatment with sertraline, and found that episodic memory and executive function improved significantly following treatment, concluding that impairments in these domains may be associated with state effects of depression. However, they did not have a control group, so they were unable to definitely determine that the cognitive change reflected a response to treatment rather than practice effects.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, 45% of individuals with LLD were cognitively impaired after one year of follow-up, and 94% of individuals with cognitive impairment at study baseline remained impaired one year later, despite reaching depression remission [13]. Others have similarly noted persistent cognitive impairment following treatment and/or remission of depressive symptoms [11,12,16,18,19], with certain risk factors, including lower baseline cognitive function, older age, later age of depression onset, and greater vascular burden associated with less improvement in specific cognitive domains [20]. Limitations of such studies, however, have included the confounding effects of practice (i.e., performance improvement resulting from repeated testing) and time (e.g., in a progressive disease such as Alzheimer's disease, the neuropathology may have progressed from the time that the patient was first tested, during the depressive episode, and the time that the patient was re-tested, after the episode resolved).…”
Section: Introductionmentioning
confidence: 99%
“…has been proposed to describe a subset of depressive disorders that occurs in old age as a consequence of cerebrovascular disease [5,22]. It has been estimated that approximately 3.4% or 2.64 million American adults 50-years and older might be considered having vascular depression [23] and treating late-life depression could improve cognitive function [24]. The change of white matter lesion volume is considered to have a causal association with vascular depression [25], but it seems more research is needed to explore the bi-directional relationship between depression and vascular disease [26].…”
Section: Discussionmentioning
confidence: 99%